2008
DOI: 10.1002/hipo.20460
|View full text |Cite
|
Sign up to set email alerts
|

Local axon collaterals of area CA1 support spread of epileptiform discharges within CA1, but propagation is unidirectional

Abstract: ABSTRACT:CA3 and subiculum are hippocampal formation regions that can initiate seizure activity because each has a substantial intrinsic excitatory connectivity. We studied the intrinsic connectivity of area CA1 by exploring the spread of synchronous population discharges in ventral hippocampal slices from rats using a recording chamber that permitted multiple simultaneous extracellular recordings along all laminae of CA1. Brief single stimulus pulses were applied to stratum oriens (SO) or stratum radiatum (SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
4
17
1
Order By: Relevance
“…The coupling direction in the CA1-CA3 indicates that the focus is complex and the seizure sources change over the duration of the discharge. It is noted that the propagation direction at the formation of CA1-CA3 seizure is unidirectional, in accordance with previous findings (Orman et al 2008).…”
Section: Application To Real Neuronal Populationsupporting
confidence: 88%
“…The coupling direction in the CA1-CA3 indicates that the focus is complex and the seizure sources change over the duration of the discharge. It is noted that the propagation direction at the formation of CA1-CA3 seizure is unidirectional, in accordance with previous findings (Orman et al 2008).…”
Section: Application To Real Neuronal Populationsupporting
confidence: 88%
“…Biological connection densities across and within cell type groupings are believed to cover the wide range of 1–50% in different areas (Thomson et al, 2002; Song et al, 2005; Orman et al, 2008). A typical number of synapses for a baseline simulation was 831,967 out of 17,888,670 (full number of possible connections: n 2  −  n for a fully connected network without self-connections), for an overall density of 4.65%, consistent with densities found in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Prior investigations reported several functional properties on the synapses between the CA1 region and the subiculum [21][22][23][24]. In these studies, stimulation of multiple presynaptic inputs was applied with an extracellular electrode to record the synaptic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Both SubPCs and CA1PCs are involved in spatial information processing as "place cells" [17][18][19][20]. Several studies on the synaptic transmission from the CA1 region to the subiculum have been reported [21][22][23][24] using extracellular stimulation protocols that activate multiple neighboring inputs from CA1PCs simultaneously, but the precise properties of the unitary monosynaptic transmission from a single CA1PC to a SubPC have not yet been provided. Thus on the functional point of view, the subiculum has been less investigated than the other hippocampal regions such as the CA1 and the CA3 regions.…”
Section: Introductionmentioning
confidence: 99%